2016
DOI: 10.3835/plantgenome2015.04.0020
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Genetic Basis of Resistance to Soybean Cyst Nematode Combining Linkage and Association Mapping

Abstract: A set of 585 informative single-nucleotide polymorphism (SNP) loci was used to genotype both a panel of diverse accessions and a set of recombinant inbred lines (RILs) bred from the cross Zhongpin03-5373 (ZP; resistant to SCN)  Zhonghuang13 (ZH; susceptible). The SNP loci are mostly sited within genic sequence in regions of the soybean [Glycine max (L.) Merr.] genome thought to harbor genes determining resistance to the soybean cyst nematode (SCN, Heterodera glycines Ichinohe). The three strongest quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 81 publications
(79 reference statements)
2
22
0
Order By: Relevance
“…This region overlapped or located closely with previously reported QTL, which were identified from PI 438489B (27.7–32.4 Mb); PI 90763 (32.4–34.1 Mb); PI 404198A (33.6–34.1 Mb); and PI 437654 (29.7–32.2 Mb) (Yue et al, 2001; Guo et al, 2005, 2006; Wu et al, 2009). This region is also close to the regions identified in a previous GWAS study for SCN resistance by Li et al (2016). Of these eight SNPs, ss715610417, ss715610420, and ss715610421 were located in the same haplotype block containing Glyma.11g234500 (GmSNAP11 ), which belonged to same SNAP family with Glyma.18g02590 (GmSNAP18 ), which is one of the Rhg1 genes (Cook et al, 2012).…”
Section: Discussionsupporting
confidence: 59%
“…This region overlapped or located closely with previously reported QTL, which were identified from PI 438489B (27.7–32.4 Mb); PI 90763 (32.4–34.1 Mb); PI 404198A (33.6–34.1 Mb); and PI 437654 (29.7–32.2 Mb) (Yue et al, 2001; Guo et al, 2005, 2006; Wu et al, 2009). This region is also close to the regions identified in a previous GWAS study for SCN resistance by Li et al (2016). Of these eight SNPs, ss715610417, ss715610420, and ss715610421 were located in the same haplotype block containing Glyma.11g234500 (GmSNAP11 ), which belonged to same SNAP family with Glyma.18g02590 (GmSNAP18 ), which is one of the Rhg1 genes (Cook et al, 2012).…”
Section: Discussionsupporting
confidence: 59%
“…Since the distribution of FI values was continuous, the most likely genetic basis of resistance in common bean is quantitative in nature. Likewise, many studies conducted on soybean also indicated a complex genetic architecture of SCN resistance [35, 36]. Many of the highly resistant accessions in the common bean core collection could be used in breeding programs to start introgression of resistance into elite/adapted germplasm and commercial cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Since SCN resistance loci in soybean are already known, we focused the search for candidate genes in common bean genomic regions based on previous information available in soybean. In soybean, linkage mapping and association analysis studies enabled the identification of rhg1 on chromosome 18 in Peking, PI88788, PI209332, and PI437654, while a second locus, Rhg4 on chromosome 8, was found in Peking, PI209332, and PI437654 [11, 12, 36]. Fine mapping of the rhg1 locus on chromosome 18 confirmed that the copy number variation of a genomic segment spanning three genes (Glyma.18g02580, Glyma.18g02590 and Glyma.18g02610 within a 31 kb rhg1-b region of PI88788) was required to confer resistance [11].…”
Section: Resultsmentioning
confidence: 99%
“…GWAS has been shown to be successful in studies investigating the genetics of SCN in soybean [48]. Li et al [49] mapped a 6-Mb region of chromosome 15 to be associated with SCN. In this report, this region has been narrowed to a less than 2-Mb region.…”
Section: Plos Onementioning
confidence: 99%